Moulding Discipline Character In Daily Activities Of Students At An Nur Islamic Boarding School Ngrukem Bantul - Rizky Ayu Ningsih; Zulkipli Lessy (ASTEEC, 2023)
This research is motivated by the existence of students who are not disciplined, so they need to get used to a disciplined attitude, with the aim of forming students' character. The aim of this research is to describe efforts to accustom students to be disciplined in their daily activities at the Annur Islamic boarding school. This research uses a qualitative approach and the technique used is a case study. The data collection techniques used were interviews, observation, and relevant documentation. The technique for soliciting informants is the purposive sampling. Next, data analysis was carried out with the stages of data collection, data reduction, data presentation, and verification. The data validity technique is triangulation. The results of the research show that the importance of habituating students' disciplined attitudes is so that students are comfortable in conducting their activities and are accustomed to and equipped with after graduating the boarding school. The habit of discipline is realized by having a regular schedule of activities every day. Daily activities include congregational prayers, dhikr after prayer, recitation, schools including Senior High School and Madrasah Diniyyah, daily complex pickets, dziba'an every Friday night, and mutual cooperation every Friday. The activity schedule is closely related to applicable regulations, where there is a management structure that monitors students in their daily activities so that those who violate them will receive sanctions.